Development and validation of a self-perception instrument for critical media literacy in Chilean pre-service teachers - Neira, Angie; Fuentes-Riffo, Karina; Vine, Ana; García, Fabián; Naranjo, Gisella (Frontiers in Education, 2024)
IntroductionThe influence of mass media and social media has profoundly impacted the way individuals access, interpret, and engage with information. It is becoming increasingly important to gain an understanding of media literacy practices, particularly among those who influence children and young people. In Spanish, there is little knowledge about critical literacy practices related to media content. This study aims to develop and validate a self-perception instrument designed to measure critical media literacy practices among Chilean pre-service teachers.MethodA structured written questionnaire with closed-ended questions was designed and validated. The instrument encompasses three dimensions: situating discourse within sociocultural contexts, recognizing and participating in discursive practices, and assessing the impact of media on the community and the individual. It comprises 28 first-person statements, rated on a five-point Likert scale.ResultsThe content was validated by a panel of experts in education, linguistics, and journalism in two phases, resulting in a high inter-rater agreement (κ = 0.78) and a content validity coefficient (CVC) of 0.97. A pilot study was conducted with 92 undergraduate students enrolled in teacher education programs. Exploratory factor analysis confirmed a three-factor structure that aligns with the proposed dimensions, explaining 51% of the total variance. Internal consistency analyses showed strong reliability, with a Cronbach’s alpha of 0.84 and McDonald’s omega of 0.85.DiscussionThe results indicate that the instrument is valid and reliable for assessing self-perceived critical media literacy practices. The findings underscore the need for educational interventions to enhance students’ ability to critically engage with media content.